When overextended surface allocation turns to groundwater: a Q methodology of well users in Oregon’s high desert - Haeffner, Melissa; Cowal, Janet; Walker, Brandy; McClellan, Clare (Frontiers in Environmental Science, 2024)
Since legal and political battles over surface water allocation in Klamath County, Oregon, USA, have gained national attention, earning the name "Water Wars," the County has been increasingly turning to groundwater to compensate for water shortfalls. This case study aims to identify the nuanced perspectives of groundwater well users who are affected by groundwater extraction. We use a hydrosocial lens to show how human actors co-evolve with water systems through a back-and-forth between groundwater abstraction, water flows, and human values. Using Q methodology, we uncover groundwater well users' perceptions and to what extent they think water problems are dealt with fairly. We identify four water perspectives that differ in the degree to which respondents prioritize clean water accessibility, industry accountability, individual responsibility for water management, and trust in governments to manage water competently. This research contributes to the growing body of literature reshaping our understanding of human-water relations by exploring different water axiologies. Understanding the nuanced discourses within these spaces helps us critically reflect upon how water management decisions affect individuals and may help practitioners avoid sociohydrological paradoxes that result from neglecting minority, but important, voices.